Natural dynamic characteristics of volumetric steel modules with gypsum sheathed LSF walls: Experimental study. (October 2021) - Alembagheri, M.; Sharafi, P.; Rashidi, M.; Bigdeli, A.; Farajian, M.
Abstract: As part of a research on structural response of modular buildings and assemblages, this experimental study investigates the effects of gypsum sheathed light-gauge steel stud walls on the natural dynamic characteristics of modular steel frames. A full-scale volumetric steel module is instrumented with sensitive accelerometers connected to a data acquisition system, to study the effects of different infill wall configurations. To this end, the module's sides are covered with bare light gauge steel frames and then different configurations and arrangements of gypsum plasterboard linings. The module's acceleration responses are recorded during free and ambient vibration tests for each case. Then the operational modal analysis is conducted on the recorded data using output-only algorithms to extract the main dynamic characteristics of the steel module, including natural frequencies, mode shapes, and modal damping ratios. The contribution of different configurations and arrangements of infill walls to the response are examined and their effects are discussed. It is observed that the infill walls can change the dynamic characteristics of the modular steel frame more than the level suggested by the design specifications, such as 30–50% reduction by ASCE7-16.